2007
DOI: 10.1097/bpo.0b013e31815a5fd3
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Bone Cyst Recurrence in Children

Abstract: The recurrence rates of primary ABC seemed to be higher in younger children. Considering the high cure rates with intralesional procedures even after recurrence, we suggest less aggressive intralesional procedures even in patients with mentioned risk factors; however, the patients' family should be informed about the high probability of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 26 publications
2
57
0
5
Order By: Relevance
“…Adjuvant radiation therapy is associated with excellent control of ABCs, ranging from 83 to 100 % local control [22,24,26,29,45]. However, complications from radiotherapy include chronic effects that can impair function and secondary malignancies, which have prevented its adoption into widespread practice.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…Adjuvant radiation therapy is associated with excellent control of ABCs, ranging from 83 to 100 % local control [22,24,26,29,45]. However, complications from radiotherapy include chronic effects that can impair function and secondary malignancies, which have prevented its adoption into widespread practice.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] En nuestra serie, hemos encontrado una relación con significancia estadística úni-camente entre QOA con contacto fisario y recidiva. A su vez, observamos mayores tasas de recidiva en pacientes de sexo femenino (45% frente al 28% en el sexo masculino), y en pacientes <10 años de edad; en estos casos, no se logró la significancia estadística, probablemente por el escaso tamaño de la muestra.…”
Section: Discussionunclassified
“…Total patellectomy or a patellar prosthesis is recommended for aggressive lesions that disrupt the patellar articular surface [10,13]. Recurrence rates after curettage vary widely from 9% to 71%, with lesions of the humerus and femur most common [1,4]. Some authors have reported higher recurrence rates with aneurysmal bone cysts in children younger than 15 years [20].…”
Section: Discussion and Treatmentmentioning
confidence: 99%